Gorbachev, Yeltsin, and the last days of the Soviet Empire / Neil Felshman. - Felshman, Neil. (St. Martin's Press, 1992)
This is a history of the most riveting true story of our age - the collapse of the Soviet Union and the end of a thousand-year empire. In 1991, the world watched in wonder as the Soviet Union's monolithic government collapsed under the weight of its unwieldy power. Now, in a dramatic and informative book, Neil Felshman recounts these momentous recent events and describes the careers of the noteworthy personalities, including the rise and fall of Mikhail Gorbachev, one of the century's most influential statesmen, and the fall and rise of Boris Yeltsin, Communist Party functionary turned democrat. Gorbachev, Yeltsin, and the Last Days of the Soviet Empire tells the story of the newest Russian revolution with glimpses into what goes on behind the headlines from Moscow, and also provides an important overview of the rich political heritage of the Russian people - background that is integral to an understanding of present-day events.